Marketing Strategy at Hotel Sentral Cawang, East Jakarta - Anik Yuniati; Yulianti; Jaja Miharja; Mita Purnamasari; Felmiwati Sendow (International Journal of Travel, Hospitality and Events, 2023)
Purpose:  This study aims to analyze the marketing strategy at Hotel Sentra Cawang, East Jakarta and To find out the marketing strategy at Hotel Sentral Cawang East Jakarta. Research methods: This study uses a qualitative approach to determine the SWOT analysis on the strategy marketing at the Central Cawang Hotel, East Jakarta. This tool compiles the company's strategic factors and uses a matrix TOWS or SWOT matrix and internal and external matrices. Results and discussion: From the identification of internal and external strategic factors, it is known that the position and profile of Hotel Sentral Cawang, East Jakarta, has a strong market competitive position in the industry. Hotel Sentral Cawang, East Jakarta, must improve product quality, facilities, service, and distribution. Implication: TO find out the condition of the Central Cawang Hotel strategically based on SWOT analysis. Then, according to the SWOT Matrix, determine a marketing strategy with 7P marketing (Product, Price, Place, Promotion, People, Physical Evidence, Process). This research was tested using SWOT analysis by identifying internal and external factors and then formulated in the Cartesian diagram, Internal and External Matrix, and SWOT Matrix. The position of Hotel Sentral Cawang, East Jakarta, on the results of the Cartesian Diagram Analysis, is in Cell 1, in a growth and development position, which is a substantial market competitive position. In the SWOT Matrix, Hotel Sentral Cawang, East Jakarta, can use four alternative strategies: the So, Wo, ST, and WT strategies.   Keywords: SWOT Analysis, SWOT Matrix, Marketing Strategy